The Relationship Between Basic Immunization Completeness and The Growth and Development of Children Aged 11-24 Months at Srikandi Husada Clinic, Kudus Regency - Erra Ardika; Ika Tristanti; Diah Andriani Kusumastuti (CV. Inara, 2026)
Children who have completed a complete series of basic immunizations are more likely to have optimal growth status and development in accordance with their age stages, when juxtaposed with children who have not completed the basic immunizations. This phenomenon can be explained by the fact that basic immunization contributes to building the immune system which further allows children to absorb nutrients properly and prevent diseases so that growth and development in children can occur optimally. This study aims to investigate the relationship between basic immunization completeness and the growth and development of children aged 11-24 months. This study uses an analytical observational research design with a cross sectional approach. All children aged 11-24 months at Srikandi Husada Clinic, Kudus Regency involved a population selected as a sample through purposive sampling techniques. The data was analyzed using the Spearman Rho test. The results showed that out of 59 children, 31 children received complete basic immunization and 28 children did not receive complete basic immunization. The percentage of growth increased by 55.9%, the percentage of growth did not increase by 44.1% while the percentage of development in accordance was 54.2%, doubtful by 27.1% and deviation by 18.6%. The results of the analysis indicated that the completeness of basic immunization was related to the growth of children with a p-value of 0.014<0.05 and an r value of 0.319. Meanwhile, in the aspect of child development, a p-value of 0.000<0.05 was obtained with an r value of 0.494 which indicates that the completeness of basic immunization is related to child development. So, it can be concluded that there is a relationship between the completeness of basic immunization and the growth and development of children aged 11-24 months at the Srikandi Husada Clinic, Kudus Regency.